Coprecipitation experiment with Sm hydroxide using a multitracer produced by nuclear spallation reaction: A tool for chemical studies with superheavy elements. (December 2016) - Kasamatsu, Yoshitaka; Yokokita, Takuya; Toyomura, Keigo; Shigekawa, Yudai; Haba, Hiromitsu; Kanaya, Jumpei; Huang, Minghui; Ezaki, Yutaka; Yoshimura, Takashi; Morita, Kosuke; Shinohara, Atsushi
Abstract: To establish a new methodology for superheavy element chemistry, the coprecipitation behaviors of 34 elements with samarium hydroxide were investigated using multitracer produced by a spallation of Ta. The chemical reactions were rapidly equilibrated within 10 s for many elements. In addition, these elements exhibited individual coprecipitation behaviors, and the behaviors were qualitatively related to their hydroxide precipitation behaviors. It was demonstrated that the ammine and hydroxide complex formations of superheavy elements could be investigated using the established method. Graphical abstract: Highlights: We established a new methodology for superheavy element (SHE) chemistry. Coprecipitation behaviors of 34 elements with Sm hydroxide could be simultaneously investigated by using multitracer. The complex formations were investigated from the coprecipitation behaviors. The established method will lead to the study on various precipitates of SHEs.